Paul and the Ancient Letter Form - Porter, Stanley E.; Adams, Sean A. (Pauline Studies, 2010)
This volume seeks to advance the discusison of Paul's relationship to Greek epistolary traditions by evaluating the nature of ancient letters as well as the individual letter components. These features are evaluated alongside Paul's letters to better understand Paul's use and adaptations of these traditions in order to meet his communicative needs.